KONTRIBUSI KSPPS BMT IBAADURRAHMAN DALAM MENINGKATKAN LITERASI KEUANGAN SYARIAH PADA ANGGOTA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sharia financial literacy refers to an individual's ability to understand, manage, and utilize financial products based on Islamic principles. Low literacy levels hinder optimal utilization of Islamic financial services. This study aims to analyze the contribution of KSPPS BMT Ibaadurrahman in improving members’ sharia financial literacy. This study employed a quantitative survey method with 60 respondents selected using simple random sampling. Data were collected through questionnaires, interviews, and documentation. Analysis techniques included validity and reliability tests, classical assumption tests, simple linear regression, t-test, and coefficient of determination. The results show a positive and significant effect of BMT contribution on sharia financial literacy. The regression equation is Y = 10.52 + 0.68X, with a correlation coefficient of 0.79 and R² of 0.62. This finding highlights the strategic role of Islamic microfinance institutions in enhancing financial literacy and inclusion.